Impact of Oil Price Shocks on GCC Stock Markets: Tail-Driven MTNARDL Evidence - Somar Al-Mohamad; Ammar Jreisat; Imad Chehade; Nasser El-Kanj; Altin Hoti (Emerging Science Journal, 2026)
This paper examines the asymmetric impact of recent oil price fluctuations on stock markets in the Gulf Cooperation Council (GCC) region from 2019 to 2024, a period marked by the COVID-19 pandemic and the prolonged Ukrainian crisis. Using the Nonlinear Autoregressive Distributed Lag (NARDL) and an enhanced Multiple Threshold Nonlinear Autoregressive Distributed Lag (MTNARDL) framework, the study examines whether extreme positive and negative shocks in oil prices, S&P 500, Bitcoin, and gold induce heterogeneous transmission effects on GCC equity indices. The empirical findings show that both extreme positive and negative oil price shocks exert a stronger and more persistent influence on GCC stock markets than fluctuations in global equities, cryptocurrencies, or precious metals. This confirms the dominant role of oil as a key driver of financial dynamics in oil-dependent economies, particularly during periods of heightened uncertainty. The main contribution of this study lies in the improvement of the MTNARDL specification, which allows for a clearer identification of tail-risk behavior and asymmetric volatility spillovers. The enhanced model captures multi-threshold nonlinearities more effectively than conventional approaches, offering a robust framework for policymakers and investors to better understand shock transmission mechanisms in hydrocarbon-based markets.